Expert playlist intro learn how to write a great technical book, by example - O'Reilly, Tim (O'Reilly Media, 2019)
"In this brief introduction to Tim O'Reilly's Expert Playlist, find out why he selected these books as great examples of how to write a technical book."--Resource description page.
Title from resource description page (Safari, viewed September 24, 2019)
Keywords: Technical writing; Rédaction technique; technical writing; Electronic videos